Pengaruh Program Senyum Juara Terhadap Peningkatan Penghimpunan Dana ZIS Pada Rumah Zakat - Dety Mulyanti; Rheza Fasya; Diana Farid; Muhammad Husni Abdulah Pakarti; Hendriana Hendriana (Universitas 17 Agustus 1945 Semarang, 2023)
Rumah Zakat is a philanthropic institution that manages zakat, infaq and shadaqah, as well as other social funds through community empowerment programs. With the Smile Champion program, Rumah Zakat is committed to improving the quality of education which includes beneficiary categories. This study aims to determine how significant the influence of the Smile Champion program is on the increase in ZIS fundraising in 2009-2018 at Rumah Zakat. The method used in this research is descriptive analysis method with a quantitative approach. The statistics use normality test, autocorrelation test, run test, heterodasticity test, multicollinearity test, coefficient of determination test and t test. The types and sources of data used are secondary data obtained from financial information published by Rumah Zakat. Based on the results of the study, it was concluded that the influence of the Smile Champion program on increasing the collection of ZIS funds at Rumah Zakat from 2009 to 2018 had a very positive significant effect of 48%, while 52% was influenced by other factors which were not included in the study. This is supported by the opinion of Sunyoto (2015) that an income in a goods or service company can be determined based on the quality of a product being marketed. From this research, Rumah Zakat must try to maintain the trust of muzzaki in particular and the community in general regarding the management of ZIS funds. It's a good idea to invite donors when distributing or giving to mustahik throughout the Champion's Smile Program. With the hope that professionalism that is manifested by transparency and accountability will make zakat collection continue to increase.